The Effect of Workload, Compensation, And Work Stress on Turnover Intention In Domestic Worker Placement Agencies (Case Study at PT Bakti Perdana Balayudha) - Faisal Muslighin; Yos Karimudin; Afriyadi Cahyadi; Yomeini Margareth; Zunaidah (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze the influence of workload, compensation, and work stress on turnover intention among domestic workers at PT Bakti Perdana Balayudha. The research employs a quantitative explanatory approach. Data were collected through a survey of 150 domestic workers placed in client households. The data were analyzed using multiple linear regression. A Likert-scale questionnaire was used for data collection and analyzed with SPSS. The results show that workload has a positive and significant effect on turnover intention. Compensation has a negative and significant effect on turnover intention. Work stress also shows a positive and significant effect on turnover intention. This study contributes to PT Bakti Perdana Balayudha by highlighting how workload, compensation, and stress influence turnover intention among domestic workers in the informal sector. It also emphasizes the importance of supportive compensation schemes and stress management strategies within domestic worker placement agencies